Teacher Training Management for Deep Learning Readiness in Elementary Schools - Destia Dewi Permata; Dinny Mardiana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study analyzes teacher training management in improving teacher readiness to implement deep learning at SDN Kapuk 13 Petang and SDN Jembatan Besi 01 Pagi, West Jakarta. The study was motivated by the increasing demand for teachers to adopt deep learning approaches that foster critical thinking, meaningful understanding, collaboration, and problem-solving skills among students. A qualitative case study design was employed to gain an in-depth understanding of how teacher training was planned, implemented, and evaluated in the two schools. Data were collected through interviews, observations, and documentation involving school principals and classroom teachers as the primary participants. The data were analyzed using Terry’s management functions—planning, organizing, actuating, and controlling—supported by the interactive analysis model of Miles, Huberman, and Saldaña. The findings indicate that both schools had implemented teacher training management, although the effectiveness of each management function varied. Planning included coordination, scheduling, and preparation of training materials but lacked a systematic needs assessment. Organizing involved task distribution and coordination, with differences in teacher participation and external institutional support. Training implementation combined lectures, discussions, teaching practice, reflection, and module preparation; however, practical mentoring and classroom-based coaching remained limited. Controlling was conducted through reflection, documentation, and participant feedback, although systematic classroom supervision and follow-up evaluation had not yet been fully established. The study concludes that teacher readiness to implement deep learning can be strengthened through needs-based, practice-oriented, collaborative, and continuously evaluated teacher training management.